1998
DOI: 10.1086/286175
|View full text |Cite
|
Sign up to set email alerts
|

Mass‐ and Density‐Dependent Reproductive Success and Reproductive Costs in a Capital Breeder

Abstract: For capital breeders, mass may affect reproductive potential. Reproductive expenditure may reduce future reproductive potential, particularly when resources are scarce. To test the hypothesis that reproductive success and the costs of reproduction vary according to mass and population density, we analyzed 25 yr of data on bighorn ewes (Ovis canadensis). The number of adult females was first limited by yearly removals, then allowed to triple. We found no survival costs of reproduction for ewes aged 4-7 yr. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
254
3
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 338 publications
(283 citation statements)
references
References 5 publications
18
254
3
1
Order By: Relevance
“…By contrast, high-quality mothers may experience no trade-off between maintaining their own condition and allocation to their offspring. Festa-Bianchet et al (1998) showed a higher cost of reproduction for lighter ewes at high population density. These results could also be explained by competition mechanisms.…”
Section: Discussionmentioning
confidence: 93%
“…By contrast, high-quality mothers may experience no trade-off between maintaining their own condition and allocation to their offspring. Festa-Bianchet et al (1998) showed a higher cost of reproduction for lighter ewes at high population density. These results could also be explained by competition mechanisms.…”
Section: Discussionmentioning
confidence: 93%
“…Gamma-type models (where variance increases as a function of the mean 2 ), but with an identity link function, were used for these populations. Additionally, density at Ram Mountain ( Festa-Bianchet et al 1998) and predator presence in both the bighorn sheep populations ( Festa-Bianchet et al 2006) were controlled for. Significant outliers (identified using 'cook's distance'; Fox 2002, p. 206) were removed to achieve diagnostic plots that did not reveal systematic bias (see the electronic supplementary material 1).…”
Section: (A) Study Populationsmentioning
confidence: 99%
“…This trade-oV between current reproduction and future survival is commonly referred to as the cost of reproduction (sensu Williams 1966), and this has been documented in a wide range of taxa: mammals (Clutton-Brock et al 1989;Festa-Bianchet et al 1998;Gittleman and Thompson 1988;Lambin and Yoccoz 2001;Sand 1996;Tavecchia et al 2005) including humans Homo sapiens and other primates (Anderson 1983;Bronson 1995;Dufour and Sauther 2002;Ellison 2003;Lummaa and Clutton-Brock 2002), birds (Lindén and Møller 1989;Monaghan and Nager 1997;Moreno 1989;Zammuto 1986) and plants (Obeso 2002).…”
Section: Introductionmentioning
confidence: 99%